Thermal characterization of novel 3-D printed lattice structures - Poh, Yew Teck (Nanyang Technological University, 2023)
Thermal management presents a significant challenge in several engineering applications, and researchers continue to develop new materials and structures to improve heat transfer efficiency. Paraffin wax is an example of an organic phase change material (PCM) with potential for use in latent heat thermal energy storage (LHTES), but its low thermal conductivity often necessitates its combination with high thermal conductivity metal foams to create metal foam-PCM composites (MFPCMs). Metal foams are often idealized using the Kelvin cell, and lattice structures made up of repeating unit cells with high surface area-to volume ratios and excellent heat transmission capabilities have emerged as a possible solution to improve thermal conductivity. This study explores the thermal conductivity of innovative 3D printed lattice architectures using experimental and numerical methods to investigate how printing settings, material characteristics, and lattice shape impact thermal conductivity. The researchers employed Selective Laser Melting (SLM) technology to print lattice structures with various geometries and infill densities. They used an existing test facility that utilizes a steady state absolute approach to obtain effective thermal conductivities of the novel structures and compared the data with results from ANSYS Fluent Flow simulations. The findings provide insight into the optimal lattice shape, printing settings, and material characteristics for achieving high thermal conductivity in 3D printed lattice systems